Semitauonic B decay anomaly - Fortes, E. C. F. S. [UNESP]; Nussinov, Shmuel (Amer Physical Soc, 2016)
The anomalously large experimentally measured ratios of the semitauonic decay B -> D-(*()) + tau + nu. and the corresponding semileptonic B -> D* + l + (nu) over bar (l) disagree with the predictions of the standard E.W + QCD model (SM). We briefly comment on this disagreement and on possible new physics explanations which are rather constrained and difficult to implement.